Communicative skills as a result of successful intelligence - Salas Vásquez, Betty Janeth (2020)
The current work began with the observation of the needs of high school students and their constant concern for the level of their development in communication skills according to the social standards of their context. Two instruments were used: The Sternberg (adapted) questionnaire (STAT), which evaluates the successful intelligence of students, where systematized quantitative information is collected as well as the teacher’s observation card to the student, for the qualitative information of the three categories of communication skills. The design is of a mixed type. Several reference works were considered in order to contrast and triangulate according to experts’ opinions.